Pengembangan Modul Elektronik Berbasis Instruksi Eksplisit pada Materi Momentum dan Impulsif Kelas XI SMA - Dina Marhami Yusra; Yulita Dwi Citra; Rosnita Rosnita (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of study: Aims to determine product development procedures and test product validity so that it meets eligibility as teaching materials. Methodology: The research procedure is carried out through the steps of developing a 4-D model, namely define, design, development, and disperse using a descriptive method. This study uses a 4-D development model and is limited to the development stage (develop). Main Findings: The results of this study indicate that the media and material expert validator stated that the electronic module based on explicit learning on momentum and impulse material had a very good proportion of 90%, so that it was declared feasible and as many as 88.67% of students were interested in learning to use the electronic module. This shows that the electronic module based on explicit learning on momentum and impulse material is very good and feasible to be used as a physics teaching material in class XI in Senior high school. Novelty/Originality of this study: The latest in this research is the basis used. Because this research is based on explicit instructions that have never been done by previous research.